The Effect of Ankle Foot Orthosis Use on the Running Speed in Post Stroke Patients: A Meta Analysis - Muhibbah Fatati; Setyo Sri Rahardjo; Hanung Prasetya (Journal of Epidemiology and Public Health, 2020)
Background: Stroke is a disease that occurs because blood flow to certain locations in the brain is disrupted. One of the main problems that occur in stroke sufferers is the disruption in the ability to walk, which will cause a decrease in the walking speed of post-stroke patients. One of the treatments used to increase the walking speed of post-stroke patients is to provide an ankle foot orthosis. The purpose of this study was to estimate the magnitude of the effect of using ankle foot orthosis on increasing walking speed of post-stroke patients by conducting a meta-analysis in the same articles.Subjects and Method: The meta-analysis was carried out by systematically reviewing the same number of articles from PubMed, Science Direct, Google Scholar, using the search keywords "ankle foot orthosis" OR "AFO" AND "Stroke" OR "patient stroke" AND "walking speed" OR